Sasuku Marriage: A Cultural Instrument in National Legal Studies - Nailatur Rahmadiah; M. Waritsul Firdaus. F (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
Each tribe has a philosophical belief in life as a social identity. Like the Minangkabau culture, there is a prohibition on marriage which is called Sapayuang marriage (Marriage of the same tribe). The same tribe in Minangkabau is prohibited from marrying even if they are far apart in generations. This pluralism certainly gives rise to legal dualism that occurs among indigenous communities. Therefore, it is deemed necessary to carry out this research to see what actually happens in society regarding tribal marriages and respond to the legal dualism that occurs in tribal marriage practices. In this writing, the author uses a type of library research. The primary data source used in this research is marriage law. One example of secondary data is books that encourage authors to develop primary data. The results of this research are that there are no sanctions regarding the prohibition of tribal marriages in the law. As long as there is no prohibition on sasuku marriage according to the law, it is legal to do so, but if sasuku marriage is carried out by the Minangkabau indigenous people they will receive sanctions, sanctions in the form of slaughtering a buffalo, being ostracized from society and some also depend on each region which determines it.